Enhanced Turnover for the P450 119 Peroxygenase‐Catalyzed Asymmetric Epoxidation of Styrenes by Random Mutagenesis. Issue 11 (25th January 2018) - Wang, Li; Wei, Siping; Pan, Xianchao; Liu, Pingxian; Du, Xi; Zhang, Chun; Pu, Lin; Wang, Qin
Abstract: A randomized library is constructed based on pET30a‐CYP119‐T214V plasmid. This library of random mutants of CYP119‐T214V was screened by means of the reduced CO difference spectra and epoxidation of styrene. By using directed evolution, a new CYP119 quadruple mutant S148P/I161T/K199E/T214V is constructed, expressed, and purified. This quadruple mutant significantly increases the turnover rate and conversion for the asymmetric epoxidation of styrene and its derivatives. The k cat. value of cis ‐β‐methylstyrene epoxidation catalyzed by the quadruple mutant exhibits an approximately 10‐fold increase, relative to the previously reported T213M mutant under the same conditions. This is the first engineered CYP119 peroxygenase for the epoxidation of cis ‐β‐methylstyrene with a high turnover rate. The proposed mechanism, on the basis of a molecular docking study, for the asymmetric epoxidation suggests that the introduction of an acidic amino acid side chain into the active site and a hydrophobic amino acid into the substrate channels of CYP119 peroxygenase might result in high efficiency for the formation of compoundI, and its subsequent peroxygenation by reconstructing the hydrogen‐bonding interaction and increasing the substrate affinity and access. Abstract : Developing enhanced mutants : A randomized library is constructed based on pET30a‐CYP119‐T214V plasmid. By using directed evolution, a new CYP119 quadruple mutant, S148P/I161T/K199E/T214V, has been constructed, expressed, and purified. This is the first engineered CYP119 peroxygenase for the epoxidation of cis ‐β‐methylstyrene with a high turnover rate (see figure).